DIRECTORS’ LIABILITY IN GERMAN LAW (World Bulletin of Management and Law, 2024)
This article provides a comprehensive overview of the legal responsibilities and liabilities of directors under German law. It explains the distinctive features of Germany’s dual-tier corporate governance system and outlines the duties and obligations imposed on directors. Key aspects covered include the Business Judgment Rule, duties of care and loyalty, and the liability of directors in cases of insolvency and actions brought by minority shareholders and creditors